Assessment of Soil Collapse and Subsurface Features Using Integrated Geophysical Methods in Bismayah Pumping Station, Southeast Baghdad, Iraq - AL-SAADY, Hussein A.; KARIM, Hussein H.; AL-MENSHED, Firas H. (GeoScience Engineering, 2022)
The Bismayah pumping station was exposed to differential subsidence in the near surface soil due to the dewatering process. The geophysical surveys via ground penetrating radar (GPR) and electrical resistivity imaging (ERI) were used to assess the subsidence in subsurface soils. Four profiles of ERI using Wenner-Schlumberger array and four lines of GPR using antenna 250 MHz were implemented around the pumping station. The results show many underground features that are interpreted as concrete slabs of the storm and sewage tanks. These features reflect high resistivity values on the ERT profiles and high amplitude reflections on the GPR lines. Moreover, the results revealed the existence of pipe leakage on the northern side of the station, which in turn showed a very distinctive shape and low resistivity values. However, the results do not present any evidence of the existence of soil subsidence in the area around the station area. Keywords: Bismayah pumping station; ERI; GPR; Integrated geophysical methods.